Participation at school as experienced by teenagers with physical disabilities. - Asbjørnslett M; Hemmingsson H (Scandinavian Journal of Occupational Therapy, 2008)
The purpose of this study was to investigate the experiences that teenagers with physical disabilities have of their participation at school. Fourteen students from several locations in Norway aged between 13 and 18 years took part. Data were collected through focus-group interviews and individual interviews. The analysis revealed three main themes: Just like the others-but not quite; Participation in terms of being where things actually happen and; Participation as student-teacher cooperation. A major finding was the importance the students put on being where things actually happen, this being regarded as being even more important than doing the same activities as the other students. Opportunities to increase cooperation by holding short meetings with teachers on how to solve both practical and learning problems promoted participation. The need to include the individual's experience in the concept of participation is discussed.